Landscape transition predictive model: Piraputanga River Watershed - Pereira, Thiago Ferreira; Buhler, Beatriz Ferraz; Neves, Sandra Mara Alves da Silva; Lopes, Wilkinson Lázaro; Muniz, Claumir Cesar; Oliveira Junior, Ernandes Sobreira (Desenvolvimento e Meio Ambiente, 2025)
The theme of Ecosystem Services (ES) has been the focus of several authors and is conceptualized as the processes through which natural ecosystems sustain human life. ES are divided into four classes: provisioning, regulating, supporting, and cultural. Environmental transformations, such as deforestation or degradation, directly compromise ES. Therefore, the main objective of this study was to analyze the impact of environmental transformations on changes in the natural landscapes of the Piraputanga River Watershed (PRW). Data related to land use and land cover, deforestation, and loss of water surface were obtained from the MapBiomas project, and fire data were obtained from the INPE platform. To classify the degree of landscape transformation, the degree of hemeroby was used in conjunction with a model based on linear trend analysis with Monte Carlo simulations. The analyses show trends in the conversion of natural areas, such as forest and savanna formations, to agricultural and pasture uses, which in 2022 represented 40.51% of the area, equivalent to 67.74 km². There was a 40% decline in water surface area. In contrast, there was an increase in pasture areas (155%) and the number of fires (163%). The projections showed a decrease in water availability, an increase in deforestation, and expansion of pasture areas. Estimates indicate that water resources in the region will disappear by 2067, a period during which the forest will be almost completely extinct due to increased agricultural activity. It is important to highlight the need for public policies to mitigate these impacts. This work highlights the landscape transition process, which is still classified as mesohemerobiotic hemerobiosis. However, all results indicate a marked process of change, and measures must be taken to prevent the situation from worsening. The transition process in the region involves trends that affect biodiversity and the capacity of ecosystems to provide essential environmental services. Finally, future projections raise concerns regarding the loss of water resources as a crucial factor.